OS08.1.A Integrative molecular analysis of matched primary and recurrent IDH-mutant astrocytoma; an update from the GLASS-NL consortium. (5th September 2022) - Vallentgoed, W R; Hoogstrate, Y; van Dijk, E; van Garderen, K; Niers, A; van den Bent, M J; Draaisma, K; van Eijk, P; de Heer, I; Kouwenhoven, M; Kros, J M; de Leng, W; et al.
Abstract: Background: The evolutionary processes that drive tumor progression in patients with IDH-mutant astrocytoma remain largely unclear. The GLASS-NL consortium was initiated to gain insight into the molecular mechanisms underlying glioma evolution and to identify markers of progression in IDH-mutant astrocytomas. Ultimately, such markers can assist clinical decision making. Here, we present the DNA methylation profiling, RNA-sequencing and shallow whole-genome sequencing (sWGS) of samples included in the GLASS-NL study. Methods: Eligible were patients with an IDH-mutant, 1p19q non-codeleted, astrocytoma at first diagnosis who underwent surgical resection of the tumor at least twice separated by >6 months, and of whom paired tumor samples were available for analyses. Overall survival (OS) was measured from date of initial surgery. DNA methylation profiling was performed with the 850kEPIC array, and transcriptome and sWGS by NGS. After quality control, DNA methylation data of 103, expression data of 91, and sWGS data of 92 patients was available for further analysis. Methylation classes were determined according to Capper et al. and copy number alterations (CNAs) were extracted from both sWGS and DNA-methylation data. Results: 110 patients were identified from various medical centers in the Netherlands. The median time between surgical resections was 41.9 months (IQR:26.5-65.9) and after initial surgery, 63% and 22% of the patients were treated with radiotherapy or chemotherapy respectively. The proportion of samples assigned to the high grade methylation class increased three-fold at recurrence. 83% of patients that progressed from low to high grade, received treatment prior to recurrent surgery, as compared to 53% of the patients that remained low grade. Genome wide DNA methylation levels of recurrent samples were lower than that of initial samples. This difference is explained by the increased number of high grades at recurrence, since near identical DNA methylation levels were observed in samples that remained low grade. Analysis of CNAs revealed chromosomal arms that were more frequently altered in high grade samples. Univariate analysis showed that losses in 3p, 9p, 10q, 13q and 14q were associated with poor OS. More than 800 differentially expressed genes between initial and recurrent tumor samples were found. Chromosomal enrichment analysis revealed a locus on chromosome 6 enriched with histone genes, to be significantly up-regulated over time. Conclusion: Longitudinal methylation profiling of IDH-mutant astrocytoma reveals a shift towards a higher grade at tumor recurrence coinciding with reduced DNA methylation levels, and increased frequency of CNAs. Longitudinal expression analysis showed changes in expression of >800 genes, including an up-regulated locus enriched with histone genes. Further integrative analyses are ongoing and will be reported at the meeting.